Simultaneous Quantitative Determination of Nonoxynol-9, Acrylamide, Sorbic Acid and Sodium Cyclamate in Toothpaste by HPLC-MS/MS - Zhang, Jun-Xian; Miao, Ming-Ming; Niu, Xue-Mei; Wang, Su-Juan; Han, Yi; Zhang, Ke-Qin; Zhang, Cheng-Ming (Asian Journal of Chemistry, 2015)
A new method for simultaneous determination and quantitation of nonoxynol-9, acrylamide, sorbic acid and sodium cyclamate in toothpaste has been developed by using high performance liquid chromatography-Tandem mass spectrometry (HPLC-MS/MS). The method is simple, sensitive and rapid. Recoveries were mostly higher than 90 %, method detection limits (MDLs) ranged from 1.69-2.77 ng mL-1 and method quantitation limits (MQLs) were included between 5.63-9.22 ng mL-1. Matrix effect was evaluated and quantitation was performed by referring to a matrix matched calibration curve to improve accuracy. This method was also applied to commercial toothpaste samples with good results.